2021
DOI: 10.3390/ijerph18168430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home Exercise Training in Patients with Nonspecific Low-Back Pain: A Systematic Review and Meta-Analysis

Abstract: Background: Exercise therapy is recommended to treat non-specific low back pain (LBP). Home-based exercises are promising way to mitigate the lack of availability of exercise centers. In this paper, we conducted a systemic review and meta-analysis on the effects of home-based exercise on pain and functional limitation in LBP. Method: PubMed, Cochrane, Embase and ScienceDirect were searched until April 20th, 2021. In order to be selected, studies needed to report the pain and functional limitation of patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 72 publications
(525 reference statements)
5
37
0
1
Order By: Relevance
“…Our pain improvement findings were consistent with previous research about the effectiveness of exercise training on decreasing chronic MSK pain [36][37][38][39][40]. For low back pain, Quentin et al's meta analysis of 13 studies reported that home-based exercise training decreased low back pain versus control groups (effect size = − 0.97, 95% CI − 1.14 to − 0.79) [36]. Skelly et al's meta analysis reported that exercise was associated with decreased back pain versus control groups at short-term (11 trials, pooled difference − 1.21 on a 0 to 10 scale, 95% CI − 1.77 to − 0.65), intermediate-term (5 trials, − 0.85, 95% CI − 1.67 to − 0.07), and long-term (1 trial, difference − 1.55, 95% CI − 2.76 to − 0.34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our pain improvement findings were consistent with previous research about the effectiveness of exercise training on decreasing chronic MSK pain [36][37][38][39][40]. For low back pain, Quentin et al's meta analysis of 13 studies reported that home-based exercise training decreased low back pain versus control groups (effect size = − 0.97, 95% CI − 1.14 to − 0.79) [36]. Skelly et al's meta analysis reported that exercise was associated with decreased back pain versus control groups at short-term (11 trials, pooled difference − 1.21 on a 0 to 10 scale, 95% CI − 1.77 to − 0.65), intermediate-term (5 trials, − 0.85, 95% CI − 1.67 to − 0.07), and long-term (1 trial, difference − 1.55, 95% CI − 2.76 to − 0.34).…”
Section: Discussionsupporting
confidence: 92%
“…Our pain improvement findings were consistent with previous research about the effectiveness of exercise training on decreasing chronic MSK pain [36][37][38][39][40]. For low back pain, Quentin et al's meta analysis of 13 studies reported that home-based exercise training decreased low back pain versus control groups (effect size = − 0.97, 95% CI − 1.14 to − 0.79) [36].…”
Section: Discussionsupporting
confidence: 90%
“…Lumbar spine physio-exercise program should be the first step towards recovery, by increasing fitness, strength and flexibility. [ 33 ]…”
Section: Methodsmentioning
confidence: 99%
“…Range of motion, stretching, and attention to proper posture are critical. [ 33 ] Addressing any kinetic, postural, or ergonomic issues will be a helpful adjunct. Inciting activities during prolonged sitting/standing and practicing good, erect posture are key.…”
Section: Methodsmentioning
confidence: 99%
“…At present, IVDD therapy generally includes conservative symptomatic and surgical treatments ( Park et al, 2021 ). Conservative treatment usually exhibits good results for LBP ( van Middelkoop et al, 2011 ; Quentin et al, 2021 ). It primarily includes oral drugs (including opioids, non-steroidal anti-inflammatory drugs (NSAIDs), skeletal muscle relaxants, acetaminophen), epidural steroid injections, and physical therapy.…”
Section: Current Treatments For Intervertebral Disc Degeneration Diseasesmentioning
confidence: 99%